The Effect Of Straw Bagasse Dust Mixture On Improving The Density (Γd) Of Silt Soil In Jorong Indobaleh Timur, Mungo, Luak District, Lima Puluh Kota Regency - Chitra Ikhwan Gani; Hanifah Asnur; Sutria Desman (Fakultas Teknik Sipil dan Perencanaan, 2025)
Silt soil has low bearing capacity and is unstable, making it unsuitable as a foundation for construction without improvement efforts. One potential soil stabilization method is by untilizing rice husk ash, wich is an agricultural waste rich in silica and possesses pozzolanic properties. This study aims to determine how the addition of rice husk ash affect the density of silt soil in Jorong Indobaleh Timur, Luak District, Lima Puluh Kota Regency. The literature review refers to soil compaction theory, soil classification according to AASTHO and USCS, and previous studies related to the utilization of local materials for soil stabilization. The research method employs an experimental approach in the laboratory of Sekolah Tinggi Teknologi Payakumbuh. Testing was conducted on original soil and soil mixtures with variations of rice husk ash at 2%, 4%, 6%, 8%, and 10% using the Standard Proctor test. The tested parameters included moisture content, maximum dry unit weight (γd max), and optimum moisture content. The result show that the original soil has a γd max of 1.07 gr/cc and an optimum moisture content of 32.55% The 4% rice husk ash mixture provides optimal results with a γd max of 1.13 gr/cc and an optimum moisture content of 34.33%, while additions beyond 4% do not significant improvement. In conclusion, the addition of 4% rice husk ash is most effective in increasing the density (γd) of silt soil, making it applicable as a local stabilization material for road construction ang light foundations.